The Effect of Low Carbohydrate Diet on Polycystic Ovary Syndrome: A Meta-Analysis of Randomized Controlled Trials - Xiaoshuai Zhang; Yang Zheng; Yanan Guo; Zhiwen Lai (International Journal of Endocrinology)
Objective. To assess the effect of a low carbohydrate diet (LCD) on women with polycystic ovary syndrome (PCOS). Methods. Data from randomized controlled trials (RCTs) were obtained to perform a meta-analysis of the effects of LCD in PCOS patients. The primary outcomes included the changes in BMI, homeostatic model assessment for insulin resistance (HOMA-IR), and blood lipids, including total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C), follicle-stimulating hormone (FSH), luteotropic hormone (LH), total testosterone (T), and sex hormone-binding globulin (SHBG). Results. Eight RCTs involving 327 patients were included. In comparison with the control group, the LCD decreased BMI (SMD = −1.04, 95% CI (−1.38, −0.70), P<0.00001), HOMA-IR (SMD = −0.66, 95% CI (−1.01, −0.30), P<0.05), TC (SMD = −0.68, 95% CI (−1.35, −0.02), P<0.05), and LDL-C (SMD = −0.66, 95% CI (−1.30, −0.02), P<0.05). Stratified analyses indicated that LCD lasting longer than 4 weeks had a stronger effect on increasing FSH levels (MD = 0.39, 95% CI (0.08, 0.71), P<0.05), increasing SHBG levels (MD = 5.98, 95% CI (3.51, 8.46), P<0.05), and decreasing T levels (SMD = −1.79, 95% CI (−3.22, −0.36), P<0.05), and the low-fat and low-CHO LCD (fat <35% and CHO <45%) had a more significant effect on the levels of FSH (MD = 0.40, 95% CI (0.09, 0.71), P<0.05) and SHBG (MD = 6.20, 95% CI (3.68, 8.72), P<0.05) than the high-fat and low-CHO LCD (fat >35% and CHO <45%). Conclusion. Based on the current evidence, LCD, particularly long-term LCD and low-fat/low-CHO LCD, may be recommended for the reduction of BMI, treatment of PCOS with insulin resistance, prevention of high LDL-C, increasing the levels of FSH and SHBG, and decreasing the level of T level. Together, the analyzed data indicate that proper control of carbohydrate intake provides beneficial effects on some aspects of PCOS and may represent one of the important interventions improving the clinical symptoms of affected patients.